ANALISA KONTRIBUSI PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH KOTA BATAM TAHUN 2009-2013 - Santoso, Cahyo Budi (Universitas Riau Kepulauan, 2014)
As one source of revenue that has significant potential, local taxes should get special attention in its management. This is supported by the heavy use of the services provided by the government to individuals and private parties, so that the government has the opportunity to optimize the tax collection area. This study aims to determine the amount of tax revenue targets of advertisement tax of Batam and its acquisition in order to know its contribution toward local revenue of Batam City in period 2009 â€“ 2013. This study uses descriptive qualitative analysis technique. The author uses descriptive type which is intended to give a clear picture of the issues examined about increasing revenue through advertisement tax management. The result showed that the advertisement tax revenues were in increasing each year except in 2010 due to the reduction of taxable objects. Moreover the average contribution of advertisement tax revenue toward local revenue of Batam City was 1,5% annually. The growth of the contribution of advertisement tax revenue in between year 2009 thru 2013 was declining.Â Keywords : Advertisemenet Tax, Local Revenue, Targets and Acquisition